Efficacy of Intravenous Ibuprofen and Paracetamol on Postoperative Pain and Tramadol Consumption After Arthroscopic Shoulder Surgery: A Prospective, Randomized, Double-blind Clinical Trial - Muhittin CALIM; Serdar YESILTAS; Mustafa GUNAY; Ismail SUMER; Sedat AKBAS (Medeniyet Medical Journal)
Objective: Efficient pain management following arthroscopic shoulder surgery plays a crucial role in decreasing pain intensity, tramadol consumption, and related side effects. This study primarily aimed to examine the analgesic impact of intravenous (IV) ibuprofen and paracetamol on postoperative pain intensity. In addition, as secondary objectives, the study assesses tramadol consumption, determine the global satisfaction score (GSS), analyze hemodynamic parameters, and investigate tramadol-related side effects. Methods: In this study, we enrolled sixty-four patients who were scheduled to undergo arthroscopic shoulder surgery and met the inclusion criteria of having American Society of Anesthesiologists scores between 1 and 3 and falling within the age range of 18 to 85 years. All participants were managed using IV patient-controlled analgesia. These patients were then randomly assigned in a double-blind manner to two groups: one receiving paracetamol (n=32), and the other receiving ibuprofen (n=32). Demographic information, visual analog scale (VAS) and GSS data, hemodynamics, tramadol consumption, and tramadol-related side effects were recorded. Results: There were no significant differences between the two groups regarding demographics, hemodynamics, GSS scores, and tramadol side effects (respiratory depression, pruritus, urinary retention, and nausea and vomiting). VAS scores of the two groups were similar at postoperative 1st, 6th, and 12th hours. However, group ibuprofen significantly reduced the VAS scores at the postoperative 24th hour (p=0.039). On the other hand, the two groups showed no significant differences in GSS scores. Compared with total tramadol consumption during the postoperative 24-hour period, ibuprofen significantly reduced tramadol consumption (p=0.003). Conclusions: The findings of this study indicate a significant reduction in both pain intensity and tramadol consumption when IV ibuprofen was administered 24 hours following arthroscopic shoulder surgery, in comparison with the use of IV paracetamol.